Alexithymia and Nutritional Factor Towards Primary Dysmenorrhea - Christiana, Elisa; Nugrahani, Cantika Iva; Noviandry, Hilmah; Himawati, Ernia Haris (Jurnal Kesehatan - STIKes Prima Nusantara, 2023)
Background: Primary dysmenorrhea is a menstrual disorder experienced by teenagers and young adults with complaints of pain in the lower abdomen. There are many factors cause dysmenorrhea, including alexithymia and nutritional status.  Objective : Analyzing the relationship between alexithymia and nutritional status with the primary dysmenorrhea among students in the State  Polytechnics of MaduraMethod: Using a quantitative design with a cross-sectional approach. The sample was 148 respondents with the simple random sampling technique by using the Toronto Alexithymia scale (TAS-20) questionnaire and the nutritional assessment form.Results: There is a significant relationship between alexithymia and nutritional status with the primary dysmenorrhea among students in the State  Polytechnics of Madura (p value = 0.001) and age of menarche with the incidence of dysmenorrhea (p value = 0.038)Conclusion: Alexithymia and nutritional status are the risk factors which have a significant relationship contributed with the incidence of dysmenorrhea among the young adolescent girl